EKSPLORASI HASIL BELAJAR MAHASISWA MELALUI PENGGUNAAN KUIS DAN TUGAS PADA E-LEARNING EDMODO DI ERA PANDEMI COVID-19 - Trisniawati Trisniawati; Nelly Rhosyida; Mahmudah Titi Muanifah (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2020)
This study aims to describe student learning outcomes through quizzes and assignments on e-learning edmodo in the covid-19 pandemic era. This study also aims to determine the implementation of learning through edmodo by utilizing features in edmodo such as uploading material, videos, poll, quiz, and assignment. The subjects of this study were the second semester student’s elementary school education program of the Sarjanawiyata Tamansiswa University who were taking elementary school mathematics classes. The instrument used was in the form of multiple choice questions, essay, and true false statements. The results obtained by the 2D class obtained an average quiz score of 78.81 and an average grade of 72.85; Class 2E obtained an average quiz score of 83.14 and an average grade of 70.23; and grade 2I obtained an average quiz score of 92.23 and an average grade of assignments of 73.12. Student learning outcomes in all three classes namely 2D, 2E and 2I are included in both categories so that learning using edmodo can be implemented well and can further be modified with other e-learning platforms.